2018
DOI: 10.1155/2018/7571954
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Maintaining a Healthy Vaginal Environment by TwoLactobacillusStrains Isolated from Cocoa Fermentation

Abstract: Bacteria in the genera Mycoplasma and Ureaplasma do not have cell walls and therefore interact with host cells through lipid-associated membrane proteins (LAMP). These lipoproteins are important for both surface adhesion and modulation of host immune responses. Mycoplasma and Ureaplasma have been implicated in cases of bacterial vaginosis (BV), which can cause infertility, abortion, and premature delivery. In contrast, bacteria of the genus Lactobacillus, which are present in the vaginal microbiota of healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 57 publications
1
14
0
Order By: Relevance
“…However, the degree of the inhibitory effects of these strains on pathogen adhesion was not consistent. The current observations partially elucidated the mechanisms by which Lactobacillus preparations successfully antagonized pathogenic infections in clinical trials and showed that these effects were different (9,25,33).…”
Section: Effects Of Lactobacillus On Pathogen Adhesionmentioning
confidence: 80%
See 1 more Smart Citation
“…However, the degree of the inhibitory effects of these strains on pathogen adhesion was not consistent. The current observations partially elucidated the mechanisms by which Lactobacillus preparations successfully antagonized pathogenic infections in clinical trials and showed that these effects were different (9,25,33).…”
Section: Effects Of Lactobacillus On Pathogen Adhesionmentioning
confidence: 80%
“…These results indicated that the source of the VECs could affect the adhesion of the same Lactobacillus. The results could explain the differences in the effectiveness of Lactobacillus preparations in different populations (9,25,33) and the necessity of clinical trials to verify the antipathogenic effects of Lactobacillus preparations. The descending order of the five Lactobacillus strains based on the strongest adhesion to both types of VECs was 4#, 3#, 5#, 2#, and 1# (Figure 1).…”
Section: Adhesion Of Lactobacillus To Vecsmentioning
confidence: 99%
“…Accordingly, more probiotic interventional studies have been conducted on reproductive failures with lactobacilli imbalance, such as adverse pregnancy outcomes [ 16 ], a significant decrease in endometrial implantation [ 36 ], and altered IVF outcomes [ 62 , 63 ]. The Lactobacillus genus has optimal probiotic properties, including high hydrophobicity and self-regulation, adhesion to epithelial cells and acid production [ 64 ], and restoration of healthy urogenital microbiota [ 65 , 66 , 67 ]. In this systematic review, combinations of Lactobacillus strains were also administered in most studies, as L. acidophilus KS400 was present in all formulae administered as single probiotic strain.…”
Section: Discussionmentioning
confidence: 99%
“…The vaginal microbiota in most healthy women of reproductive-age is dominated by protective Lactobacillus species that are thought to reinforce the defense against invasion and colonization by pathogenic microorganisms (Melgaço et al, 2018). In women with vaginal infections, such as BV and VVC, the dominance of these Lactobacilli is compromised (Sobel, 2007).…”
Section: Introductionmentioning
confidence: 99%